Pemetaan Potensi dan Pola Pertumbuhan Ekonomi dalam Mengurangi Ketimpangan Wilayah Kabupaten Mojokerto - Mohammad Wasil; Mohammad Wahed (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this study is to analyze what economic sectors are potential to be used as development priorities and patterns of economic growth in the economy of Mojokerto Regency. The method used is: Location Quotient, Shift Share, and Williamson Index. From the analysis of the location quotient that falls into the category of the base sector are Agriculture, Clean Water & Water Sector, Building Sector, Transportation & Communication Sector, Financial Sector, Corporate Leasing & Services, and Services Sector. And the results of the shift share analysis show that the sectors with the fastest growth are the agricultural sector, mining & quarrying sector, manufacturing industry sector, and the trade sector, and the services sector. While the results from Williamson study show that the sub-districts that have the highest level of inequality are in Mojosari sub-district, Pungging subdistrict, and Kemlagi sub-district